Radio television
Published by the International Radio and Television Organization (OIRT).Continues: SERLOC preceding entry: Documentation and information bulletin of the International Broadcasting Organization (later called International Radio and Television Organization).Continued by: SERLOC succeeding entry: Radio television international review.